A Comprehensive Analysis: The Representation of Feminism in the Movie “Losmen Bu Broto” - Khusna, Dwike Amalia; Widodo, Wahyu Unggul; Kusumaningtyas, Etika Dewi (English Education and Literature Journal (E-Jou), 2025)
In the contemporary era, discussions around gender equality and women's representation had gained significant traction, emphasizing the need for equal rights and opportunities regardless of gender. This research explored the portrayal of feminist values through the movie “Losmen Bu Broto,” directed by Ifa Isfansyah and Eddie Cahyono. Using Roland Barthes' semiotic framework, the research analysed how the movie represented feminism by examining the characterization of its female protagonists, including Bu Broto, Mbak Pur, and Jeng Sri. The movie, adapted from a TV series and set in a traditional Javanese context, was notable for its strong female characters who challenged societal norms. This research employed qualitative research methods, including detailed scene analysis and character examination, to investigate how these characters embodied feminist ideals. The analysis focused on various feminist theories, including Radical Feminism; Marxist and Socialist Feminism; Liberal Feminism; Black Feminism; and Postmodern Feminism, to understand how the movie's narrative reflected and critiqued traditional gender roles. The findings revealed that “Losmen Bu Broto” presented a nuanced portrayal of feminist values, illustrating women's strength, independence, and resistance to patriarchal structures. Through its characters' appearances, dialogues, and actions, the movie navigated the intersection of feminism and Javanese culture, highlighting both the challenges and advancements in the representation of women. This research contributed to the broader discourse on feminism in media by providing a comprehensive examination of how feminist ideologies were depicted and challenged within a culturally specific context